Expression of fibroblast activation protein alpha in odontogenic keratocyst and ameloblastoma: A cross-sectional immunohistochemical study - Sandhya Tamgadge; Treville Pereira (Wolters Kluwer Medknow Publications, 2023)
Introduction: Cancer has always been a mystery for the researcher, healthcare providers, and even patients. This could be because of the unexplored journey of a cell from its physiological to cancerous form. Every day, new research articles are being emerged on various platforms where researchers have been attempting to explore the hidden signals of carcinogenesis. Cancer-associated fibroblasts (CAFs) are one of the key proteins. Fibroblast activation protein alpha (FAPα) is found in normal-appearing surrounding tumor microenvironments (TMEs) and shows a strong positive correlation with high tumor grade. It has been found exceedingly expressive in oral squamous cell carcinoma. Similarly, odontogenic lesions too are highly destructive and show a high recurrence rate. Thus, there is a crucial need to assess FAPα in these lesions too. This article is a preliminary attempt to evaluate FAPα expression in ameloblastoma and odontogenic keratocyst, which are highly destructive lesions of the jaws. Materials and Methods: The study group comprised 40 cases each of odontogenic keratocyst (OKC) and ameloblastoma . A total of 10 cases each of lymphoma (5 negative control) and colorectal carcinoma (5 positive control) were selected as control. Both groups were immunohistochemically stained using FAPα antibody. The study group was compared with clinical parameters and analyzed statistically using chi-square tests to find out correlation, and phi coefficient and Cramer V test were used to test the strength of association. Kendall coefficient of rank correlation tau-sub-b (τb) was used to correlate the final immunoreactivity score (IRS) and the age and dimension of the lesion. Kappa correlation was calculated to assess interobserver variability. Results: There was a significant correlation between the extension of the lesion and the FAPα of each group. Other correlations showed insignificant correlations. But both groups showed more cases in moderate and very strong IRS. Conclusion: There is a strong correlation between the FAP expression and extension of the lesion in OKC and ameloblastoma. There was a strong role for FAPα in the pathogenesis of OKC and ameloblastoma.